1993
DOI: 10.1038/clpt.1993.196
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the acyclovir pro-drug valaciclovir after escalating single-and multiple-dose administration to normal volunteers

Abstract: The pharmacokinetics and safety of the L-valyl ester pro-drug of acyclovir, valaciclovir (256U87), were investigated in two phase I, placebo-controlled trials in normal volunteers. These included a single-dose study with doses from 100 to 1000 mg (single cohort) and a multiple-dose investigation with doses from 250 to 2000 mg (five separate cohorts). In each cohort, eight subjects received valaciclovir and four subjects received placebo. Pharmacokinetic findings for valaciclovir and acyclovir were consistent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
228
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(247 citation statements)
references
References 2 publications
16
228
3
Order By: Relevance
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…The same is not the case with VACV which may be due to rapid metabolism of VACV to ACV (Table 3). As previously reported, there is high accumulation of ACV after the administration of VACV at the recommended dosage regimens of 250 mg, 500 mg, and 1 g of VALTREX (valacyclovir hydrochloride) administered four times daily for 11 days in volunteers with normal renal function (Weller et al, 1993).…”
Section: Discussionmentioning
confidence: 56%
“…Owing to its limited bioavailability, ACV has shown moderate antiviral efficacy after oral administration (Steingrimsdottir et al, 2000). VACV has been reported to increase the oral bioavailability of acyclovir by 3-to 5-fold in humans (Purifoy et al, 1993;Weller et al, 1993). Enhanced oral absorption of acyclovir after administration of valacyclovir has been attributed to the amino acid (B 0,+ ) (Hatanaka et al, 2004) and peptide (PepT1) (Ganapathy et al, 1998) …”
Section: Introductionmentioning
confidence: 99%
“…Despite the inconsistent efficacy of acyclovir in the prophylaxis of CMV disease [2,12,161, a large multicenter study has demonstrated that oral valacyclovir (a valine ester of acyclovir) is effective in the prevention of post-RTx CMV disease [20]. The reason for this is the appreciably higher bioavailability of acyclovir after valacyclovir administration than can be obtained by the administration of oral acyclovir [32]. Flechner et al have shown that oral ganciclovir is more effective than oral acyclovir [lo]; however, no study comparing ganciclovir and valacyclovir has been conducted to date.…”
mentioning
confidence: 99%